2008
DOI: 10.1111/j.1464-410x.2008.07424.x
|View full text |Cite
|
Sign up to set email alerts
|

Total reconstruction of the vesico‐urethral junction

Abstract: additional vesico-urethral anastomotic support. Patients in 2007 (182) received the total reconstructive procedure, which included an anterior reconstruction and posterior reconstruction. Outcome data were collected using standardized health-related quality-of-life measures, which included the Expanded Prostate Cancer Index Composite survey, International Prostate Symptom Score, International Index of Erectile Function, and then re-verified by telephone interview with a standardized questionnaire. The follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 10 publications
10
141
0
2
Order By: Relevance
“…The Rocco suture was first described in radical retropubic prostatectomy by Rocco in 2007(Rocco et al, 2007 and has been reported by Tewari et al (2008) for its use in RALP. This is a posterior reconstruction to support the urethral sphincter, and it has been used in combination with the Pagano suture, which adds further reinforcement to the posterior bladder neck.…”
Section: Surgical Modificationsmentioning
confidence: 99%
“…The Rocco suture was first described in radical retropubic prostatectomy by Rocco in 2007(Rocco et al, 2007 and has been reported by Tewari et al (2008) for its use in RALP. This is a posterior reconstruction to support the urethral sphincter, and it has been used in combination with the Pagano suture, which adds further reinforcement to the posterior bladder neck.…”
Section: Surgical Modificationsmentioning
confidence: 99%
“…The pathologic stage and PSM rates for open, RLP, and RARP series are summarized on Table 4, 16-22,24-28,30,31,33,55-57 Table 5, 33,37,38,[40][41][42][44][45][46][47] and Table 6, 30,31,35,[48][49][50][51][52][53][54]58 respectively. The pathologic stage in the RARP series was of 78.2% pT 2 tumors and 20.5% pT 3 tumors.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…Early multi-institutional studies in Japan found the recovery of urinary function following LRP to be slower compared to that following retropubic radical prostatectomy (RRP) (2,3). The operative procedures used to improve the recovery of urinary continence following radical prostatectomy include preserving the fascia covering the levator ani muscle (4), preserving the bladder neck (4), preserving neurovascular bundles (NVBs) (5), securing a longer functional urethra (6,7), reconstructing the posterior musculofascial plate (PMPR) (8)(9)(10), suspending the vesicourethral anastomosis (11) and performing an anterior reconstruction (12).…”
Section: Introductionmentioning
confidence: 99%